Underutilized citrus species: An insight of their nutraceutical potential and importance for the development of functional food - Kumar, V.; Kaur, R.; Aggarwal, P.; Singh, G.
The nutritional and medicinal value of citrus fruits is well known mainly attributed to their desirable phytochemical profile. However, some citrus species are only utilized by the local folks and unknown to the other parts thus remaining underutilized. These species are abundant in bioactive compounds such as polyphenols, antioxidants, carotenoids, dietary fiber, vitamins and minerals. The various in vitro and in vivo studies confirm their potential as antioxidant, antibacterial, antiviral, anti-inflammatory, anti-diabetic, anti-cancer, anti-atherosclerosis and regulating of the glucose, cholesterol and triglycerides level in the body. This review explores a new approach to the underutilized citrus species with an emphasis on its bioactive and medicinal properties. Various attempts also have been made on the utilization of different parts of these citrus species in the food industry. The findings thus far indicate that the underutilized citrus species could be developed as a promising nutraceutical ingredient for the application in the food and pharmaceutical industry, but further studies on large scale or commercially processing of these species (particularly on bioactive compounds retention of different parts and determination of health potential as clinical trials)are recommended.
Keywords: CITRUS; FUNCTIONAL FOOD; HEALTH BENEFITS; RUTACEAE; UNDERUTILIZED